THE METHODOLOGICAL PRINCIPLES OF THE WORLD MARKET OF GOODS ANALYSIS WITH USE OF SYSTEM OF THE INTERCONNECTED ECONOMETRIC EQUATIONS - N. I. Didenko; D. F. Skripnuk (Модернизация, инновация, развитие)
The principles of the market research which are based on use of system of the interconnected econometric equations are stated in the article. The system of the interconnected equations for the analysis and market forecasting is used for the market description in cases when it is difficult to determine, what variable is dependent, and what independent. The article contains procedure of the formulation of axiomatics of the market, creation the econometric equations and checks of system of the interconnected econometric equations. There is without answer a question, whether there shall be an axiomatic basis unique, or plurality of axiomatic bases is allowed, each of which depends on understanding the specific researcher of processes in the researched market.